2015
DOI: 10.1371/journal.pone.0140956
|View full text |Cite
|
Sign up to set email alerts
|

Orientation Dependent MR Signal Decay Differentiates between People with MS, Their Asymptomatic Siblings and Unrelated Healthy Controls

Abstract: R2* relaxometry of the brain is a quantitative magnetic resonance technique which is influenced by iron and myelin content across different brain regions. Multiple sclerosis (MS) is a common inflammatory, demyelinating disease affecting both white and grey matter regions of the CNS. Using R2*, increased iron deposition has been described in deep gray matter of MS patients. Iron accumulation might promote oxidative stress in the brain, which can lead to cell death and neurodegeneration. However, recent histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(65 citation statements)
references
References 40 publications
4
60
1
Order By: Relevance
“…Compared with susceptibility tensor imaging , which is another magnetic susceptibility based fiber orientation mapping method, the T 2 * approach measures orientation using intra‐voxel field inhomogeneity information and, therefore, may be less prone to artifacts from nonlocal field inhomogeneity if the voxel size is small. Another approach using the T 2 * anisotropy is combining a single orientation T 2 * map with a DTI fiber orientation map and generating a white matter T 2 * anisotropy plot . This plot does not require multiple head rotations and may provide a good sensitivity to myelination, although spatial information is no longer available.…”
Section: Applicationsmentioning
confidence: 99%
“…Compared with susceptibility tensor imaging , which is another magnetic susceptibility based fiber orientation mapping method, the T 2 * approach measures orientation using intra‐voxel field inhomogeneity information and, therefore, may be less prone to artifacts from nonlocal field inhomogeneity if the voxel size is small. Another approach using the T 2 * anisotropy is combining a single orientation T 2 * map with a DTI fiber orientation map and generating a white matter T 2 * anisotropy plot . This plot does not require multiple head rotations and may provide a good sensitivity to myelination, although spatial information is no longer available.…”
Section: Applicationsmentioning
confidence: 99%
“…21 Perfusion maps were registered to DTI using FLIRT. Voxels with orientations within 5 intervals were pooled and averaged and then used to calculate 22 for further details on the use of DTI to measure tissue orientation.…”
Section: Data Processingmentioning
confidence: 99%
“…Furthermore, in MS lesions with profound axonal loss, the tissue orientation is also ill‐defined. However, there was almost no difference in R 2 * (θ) when lesions were included or excluded . This finding suggests that the step of lesion exclusion may be omitted for the investigation of non‐lesional WM in MS using the proposed approach.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to focal demyelinated WM lesions, diffuse alteration of the non‐lesional WM has been observed when using various MR methodologies, such as proton MR spectroscopy, magnetization transfer ratio, myelin water imaging, or R 2 * in combination with diffusion tensor imaging (DTI). By associating a measured R 2 * with a fibre orientation, θ, computed from DTI, the orientation dependent R 2 * (θ) can be calculated . Histopathological studies have revealed diffuse and extensive damage in the normal appearing white matter (NAWM), encompassing myelin loss, axonal injury, microglia activation, and perivascular inflammatory infiltrates .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation